Analisis Proses Adanya Free Trade Zone (FTZ) di Kota Tanjung Pinang - Amanda Meyza; Sri Kesuma Dewi; Nabila Salshabila (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The Free Trade Zone (FTZ) in Tanjung Pinang, established in 2008 along with the Sabang, Karimun, and Bintan zones under Government Regulation No. 41 of 2021, offers several strategic advantages. Its presence provides attractive opportunities for investors through various incentives designed to stimulate regional economic growth. The FTZ concept encourages export-oriented foreign investment and relies on strong infrastructure development to ensure that investors receive efficient and reliable services. Tax exemptions also serve as a major incentive, motivating investors to allocate their capital and thereby contributing to economic expansion. Investment activities play an essential role in accelerating national economic development and supporting both political and economic sovereignty. Through increased investment, a country can better utilize its economic potential and transform it into real economic strength, using both domestic and foreign capital. This allows developing regions to progress toward achieving levels of economic advancement comparable to more developed areas. Ports are a key element in attracting investors, as they help reduce export-related costs, especially taxes that are often relatively high. This study uses a qualitative approach with descriptive methods. Based on policy indicators, the establishment of the Bintan FTZ has not yet been fully effective, as many areas within the region still require further development.